Negative pressure wound therapy with instillation: International consensus guidelines update - Kim, Paul J.; Attinger, Christopher E.; Constantine, Thomas; Crist, Brett D.; Faust, Elizabeth; Hirche, Christoph; Lavery, Lawrence A.; Messina, Valerie J.; Ohura, Norihiko; Punch, Laurie J.; Wirth, Garrett A.; Younis, Ibby; et al. (International wound journal, 2020)
The use of negative pressure wound therapy with instillation and dwell time (NPWTi-d) has gained wider adoption and interest due in part to the increasing complexity of wounds and patient conditions. Best practices for the use of NPWTi-d have shifted in recent years based on a growing body of evidence and expanded worldwide experience with the technology. To better guide the use of NPWTi-d with all dressing and setting configurations, as well as solutions, there is a need to publish updated international consensus guidelines, which were last produced over 6 years ago. An international, multidisciplinary expert panel of clinicians was convened on 22 to 23 February 2019, to assist in developing current recommendations for best practices of the use of NPWTi-d. Principal aims of the meeting were to update recommendations based on panel members' experience and published results regarding topics such as appropriate application settings, topical wound solution selection, and wound and patient characteristics for the use of NPWTi-d with various dressing types. The final consensus recommendations were derived based on greater than 80% agreement among the panellists. The guidelines in this publication represent further refinement of the recommended parameters originally established for the use of NPWTi-d. The authors thank Karen Beach and Ricardo Martinez for their assistance with manuscript preparation.
First published: 30 October 2019
Gesehen am 12.05.2020